ELECTRICAL RESISTIVITY-BASED SUBSURFACE CHARACTERIZATION AND GEOTECHNICAL CORRELATION FOR LANDFILL SITE INVESTIGATION IN BULAKAN, CILEGON, BANTEN - Zelandi, Muhammad; Tadersi, Risnaliyah Nuriil; Kirana, Febiyora Chandra; Siregar, Anggi Deliana; Ritonga, D.M. Magdalena (JOURNAL ONLINE OF PHYSICS, 2026)
Landfill infrastructure development requires comprehensive subsurface characterization to ensure foundation stability and long-term environmental safety. This study applies Electrical Resistivity Tomography (ERT) using the Wenner electrode configuration along five survey lines (400 m length, 10 m electrode spacing) as the primary characterization method, integrated with geotechnical borehole drilling, Standard Penetration Tests (SPT), and groundwater observations at four boreholes of 10–20 m depth, to evaluate the suitability of Bukit Bulakan, Cilegon, Banten Province for landfill development. Inversion of 2D resistivity sections identifies three principal lithological units: Clayey Sand (0–150 Ω·m, SPT-N 10–36), Silty Sand (150–200 Ω·m, SPT-N 22–50), and Sandstone (200–1,300 Ω·m, SPT-N >50). Resistivity-to-SPT-N correlation demonstrates a consistent positive relationship in which increasing resistivity corresponds to increasing lithological compaction. Weak zones (47–73 Ω·m) identified along three survey lines indicate fault or fracture features that represent potential leachate migration pathways. The Sandstone layer at depths exceeding 10–15 m constitutes the most suitable foundation for landfill construction, while weak zones require targeted mitigation, including geomembrane installation and periodic ERT monitoring. This study confirms that integrating ERT with conventional geotechnical investigation provides substantially more comprehensive spatial subsurface characterization than borehole-only approaches in heterogeneous volcanic geological environments.